DECISION MAKING TO INVEST IDXHIDIV 20 STOCK WITH FUNDAMENTAL ANALYSIS - Choirun Nisful Laili; Lik Anah (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
Investing in Capital Market requires fundamental and technical analysis. For long-term oriented investors aimed to obtain dividends every year, it require an analysis of companies that are consistent in dividend distribution, which can be seen in IDXHIDIV20. The data population was a company registered in IDXHIDIV20. The data sample is determined by purposive sampling method. The results showed that ASII, HMSP, INDF, INTP, TLKM, UNTR, UNVR meet the sample criteria. The fundamental analysis showed that the highest average ROE is UNVR, the lowest average DER is INTP, the highest average of DPR is INTP, the highest average of DPS is UNTR, the highest average of EPS is UNTR, and the lowest average of PER is UNTR. Meanwhile, based on stock valuation, INDF still in the undervalued category (PER <15x, PBV <1). There were two issuers with undervalued PER categories, namely UNTR and ASII.